2005
DOI: 10.4049/jimmunol.175.3.1937
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Dependent Pulmonary Fibrosis in Adenosine Deaminase-Deficient Mice

Abstract: Pulmonary fibrosis is a common feature of numerous lung disorders, including interstitial lung diseases, asthma, and chronic obstructive pulmonary disease. Despite the prevalence of pulmonary fibrosis, the molecular mechanisms governing inflammatory and fibroproliferative aspects of the disorder are not clear. Adenosine is a purine-signaling nucleoside that is generated in excess during cellular stress and damage. This signaling molecule has been implicated in the regulation of features of chronic lung disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 62 publications
5
145
2
Order By: Relevance
“…In addition, ADA-deficient mice develop signs of chronic pulmonary injury in association with chronically elevated pulmonary adenosine levels. In fact, ADAdeficient mice die within weeks after birth from severe respiratory distress (42) and recent studies suggest that attenuation of adenosine signaling may reverse the severe pulmonary phenotypes in ADA-deficient mice, suggesting that chronic adenosine elevation can affect signaling pathways that mediate aspects of chronic lung disease (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ADA-deficient mice develop signs of chronic pulmonary injury in association with chronically elevated pulmonary adenosine levels. In fact, ADAdeficient mice die within weeks after birth from severe respiratory distress (42) and recent studies suggest that attenuation of adenosine signaling may reverse the severe pulmonary phenotypes in ADA-deficient mice, suggesting that chronic adenosine elevation can affect signaling pathways that mediate aspects of chronic lung disease (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Significant elevations in transcript levels of adenosine A 1 and A 2B receptors were also reported [64]. These changes correlated with histo-logically demonstrable fibrosis with an increased number of pulmonary myofibroblasts and collagen deposition following staining with Masson’s trichrome as well as semi-quantitative assessment of fibrosis by Ashcroft’s fibrosis scoring system [60, 64]. Excessive collagen deposition was not limited to the lungs, but was also seen in the liver and kidney glomeruli.…”
Section: Pulmonary Fibrosismentioning
confidence: 95%
“…These mice were developed in their laboratory, and targeted gene deletion resulting in the deficiency of a key enzyme that catabolizes adenosine into inosine renders both circulating and tissue adenosine levels extremely high [60, 61]. One of the potential benefits of using this model is that adenosine deaminase enzyme therapy can be administered by injection to these mice, much as it is used as therapy for adenosine deaminase in humans, thus enabling direct manipulation of tissue adenosine levels through varying the dose of adenosine deam-inase injected.…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…Activation of the A2BR on human lung fibroblasts increases the release of IL-6 and induces differentiation into myofibroblasts suggesting that adenosine, via A2BR participates in the remodelling process occurring in chronic lung diseases [64]. Chunn et al revealed that controlling adenosine levels with the use of exogenous ADA treatments may provide a significant approach to seize the progression or alter the features of pulmonary fibrosis in severe asthma [65]. …”
Section: Discussionmentioning
confidence: 99%